Analysis and Assessment of Trends in the Development of Network Retail in Ukraine - Dmytruk, Andriy (Global Prosperity, 2025)
Abstract. The article presents an analytical study of trends in the development of chain retail in Ukraine. A system of indicators for assessing the development of chain retail is proposed. Groups of indicators are identified that characterise the scaling and strategic dynamics of chain retail; the financial performance of chain retail enterprises; the financial stability and business activity of chain retail enterprises; the effectiveness of the sales activities of chain retail enterprises; and the resource and personnel efficiency of chain retail. The following chain retail enterprises were selected as research objects: Silpo Group LLC (Silpo), Fora LLC (Fora), Omega LLC (Varus), Auchan Ukraine Hypermarket LLC (Auchan), Metro Cash & Carry Ukraine LLC (Metro). An analysis of trends in the development of chain retail has shown the following results: there is a gradual recovery in turnover and income after the crisis fluctuations caused by pandemic and military factors; growth in retailers’ assets and equity, indicating an expansion of the investment base and a gradual restoration of financial stability; the industry is seeing a strengthening of operational efficiency and cost optimisation; the role of human and resource potential in shaping the competitive advantages of retail is increasing.